Elucidating the genetic variants of the type vi secretion system 5 (t6ss-5) in clinical and environmental strains of burkholderia pseudomallei and their potential correlation with the clinical courses of the human diseases - Noreafifah, Semail (2024)
Burkholderia pseudomallei, a pathogenic bacterium that causes melioidosis, is endemic in Southeast Asia and tropical Australia. Although knowledge and understanding of this neglected infectious disease have increased, the fatality rate remains high. Notably, the bacterial virulence factor type six secretion system-5 (T6SS-5) plays a significant role in this cellular internalization, yet its genetic variants and correlation with clinical outcomes of melioidosis remain unexplored. By employing multiplex PCR and whole genome sequencing (WGS) analysis, this study aimed to elucidate T6SS-5 genetic variations and their potential association with disease severity and outcome. Three multiplex PCR assays were developed for the detection of 18 genes within the T6SS-5 cluster of B. pseudomallei i.e. Assay 1: tssC-5, tagD-5, tssA-5, hcp-5, tssB-5, tssF-5, and vgrG-5; Assay 2: tssL-5, tssJ-5, tssG-5, virA-5, tagB-5, and tagAB-5; and Assay 3; clpV-5, tssE-5, tssM-5, virG-5, and tssK-5. Designing specific primers was the first step in constructing these PCR assays. The specificity and sensitivity were assessed on each individual set of primers. Clinical B. pseudomallei isolates were used to evaluate the initial accuracy of these multiplex PCR assays. Results indicated that all the designed primers for T6SS-5 gene cluster were specific to the respective target bacteria. The optimized concentrations of primers for each multiplex assay were varied for each primer pair, between 2.5 – 20.0 µM. The optimum annealing temperature for these assay was 61 °C. The limit of detection for Assay 1, Assay 2 and Assay 3 were determined to be at 103 CFU/ml, 108 CFU/ml, and 107 CFU/ml, respectively, to detect all the targeted genes in each multiplex assay. Initial evaluation of clinical isolates indicated that the assays were 100% accurate on both target and non-target bacteria (n = 28). Screening of T6SS-5 genes was conducted on 88 clinical and 2 environmental isolates. Results showed that majority of the clinical isolates (83%; n=73) and all environmental isolates (100%; n=2) were able to detect all the 18 target genes in their genomes. Variations in detection of the T6SS-5 gene cluster were seen in the tssE-5, tssM-5, virG-5, and tssK-5 genes. However, there was no significance association observed between the presence of these genes and the types of clinical presentation and outcomes of the disease. In addition to multiplex PCR analysis, WGS was performed on 18 isolates, stratified into recovered (six isolates), relapsed (four isolates), deceased (six isolates) patient groups, and environment (two isolates). A total of 1495 single nucleotide polymorphism (SNP) mutations were detected across the T6SS-5 gene cluster, with the highest mutations found in the clpV-5 gene. The non-synonymous SNPs of clpV-5, tssM-5, tssA-5, and tagAB-5 show a significant association (p value < 0.0001, < 0.0001, 0.0067, and 0.0207, respectively) with bloodstream infection among the patients. Approximately 149 insertion/deletion (indel) mutations have been identified, with notable occurrences in tssA-5, clpV-5, tagAB-5, tagC-5, and tssM-5 with 36, 72, 16, 11 and 14 mutations respectively. However, there was no significance association observed between indels mutations of these genes with the clinical presentations and outcomes of melioidosis. In conclusion, this study highlights the complexity of melioidosis pathogenesis and the importance of T6SS-5 as a virulence determinant, as well as the need for further research to unravel this virulence determinant. Understanding these genetic variants could aid in developing targeted therapies or diagnostics for melioidosis.